PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN MENGGUNAKAN MODEL PEMBELAJARAN STAD BERBANTUAN MEDIA KARTU BERGAMBAR PADA KELAS 1 SDN KARANG MEKAR MANDIRI 1 - Wiryateja Januarta (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
This study investigates the effect of implementing the STAD learning model, supported by picture card media, on improving early reading skills among first-grade elementary school students. A quantitative research approach was applied, utilizing a pretest-posttest design. The findings revealed a significant improvement, with an average score increase of 29.68 points from pretest to posttest. The significance level of p < 0.05 indicates that the method is statistically effective. Good responses from students and observations of the learning process that are running effectively support the success of implementing this method. Attractive and easy-to-understand visual media can motivate students and increase the effectiveness of learning to read, so this method is worthy of being an alternative for sustainable learning. Overall, the use of the STAD Study model with picture card media has proven capble to significantly improve the reading learning outcomes of elementary school students and can be implemented widely.